The Concept of Sustainable Corporate Development as Well as Tax Base Erosion and Profit Transfers - Bzymek-Iwanowicz, Paulina (Studia Oeconomica Posnaniensia, 2014)
The purpose of this article is an attempt to present the current problems of tax base erosion and profit transfers resulting from actions undertaken by multinational enterprises in the context of the concept of sustainable development. Additionally, this article attempts to answer the question as to whether the actions of enterprises within the field of tax optimization are consistent with the concept of sustainable development. The paper presents the concept of sustainable development and corporate sustainable development, as well as describing the problems and causes of tax base erosion and profit transfers. These considerations are the starting point for the author’s further research.